PLACES OF WORSHIP. Space and religion in Lisbon suburban configurations - Guarda, I.; Guerreiro, R.; Heitor, T. (11th International Space Syntax Symposium, 2017)
The emergence of new religious movements is a global phenomenon. Although becoming subject of inquiry by recent academic works concerned with new spiritual content and practices, the places of worship persist an overlooked subject. The aim of this research is to understand the implications of spatiality in the constitution of the new places of worship within Lisbon suburbs after the 1970’s. It analyses the relationship between place centralities and new spatial cultures and urbanities in suburban landscapes. It also analyses change and persistence of traditional pattern of sacred spaces. To pursue these aims space syntax methodology was used in order to analyse street networks configuration to understand location of places of worship. The main technic was segment analysis. The syntactic measures were calculated to understand the relationship between global and local structures and read the city as a whole (urban and suburban). Using GIS software, places of worship were mapped within Lisbon region according to different religions. The patterns of distribution are then compared with the syntactic measures. The results have confirmed the hypothesis of space dematerialization and placelessness which characterizes the new religious movements. The pattern of distribution of places of worship (factories, warehouses, shops, cinemas, etc.) in Lisbon region follow places of good accessibility (global and local). The value of space remains not in its simbology but in its accessibility and functionality.